Analyzing the Site Suitability of the Banquet halls in Jeddah using GIS - Qisi, Shrouq Mohmed; Elsheikh, Ranya Fadlalla Abdalla (Journal of Humanities & Social Sciences, 2019)
The objectives of this study are to determine the criteria of the halls site selection according to conditions approved by the Ministry of Municipality and then evaluate the current distribution of the services of the halls in Jeddah City and analyze the appropriateness of this distribution to serve the population of Jeddah using spatial statistical methods by GIS program.The results revealed that the distribution of the banquet halls is clustered and the general trend of distribution of the banquet halls extends from the northeast to the southeast. The indicators of the spatial evaluation revealed that all the halls do not offer their services as required, as there are large areas within the city do not reach the services due to poor spatial distribution and their location do not meet the criteria approved by the Ministry of Municipality. 53% of the hall sites do not match the first condition, which states that the location of the hall should be on the intersection of two streets (one main). 75% of the hall sites match the second condition that the distance between the project site and the nearest hospital is less than 500 meters and 61% with the criterion of distance from mosques and places of worship should not be less than 250 meters. On other hand, more than 95% of hall sites correspond positively to the requirement distances from the gas selling places and 50% of hall sites correspond negatively from other wedding halls.
Keywords: geographic information systems; spatial analysis; standards; evaluation